Analisis Manfaat Program AKLAM dalam Peningkatan Pemanfaatan Laboratorium Fisika - Muhammad Qaddafi; Santih Anggereni; Muh. Syihab Ikbal; Mukti Ali; Nur Ika Akbar (Pendidikan Fisika UIN Alauddin Makassar, 2023)
This research is a Mixed Methods research with a concurrent triangulation research design, The objectives of this study are: 1) To find out the picture of the arrangement of school laboratory governance after the application of student laboratory work (AKLAM) of the Physics Education study program UIN Alauddin Makassar in the Takalar and Bulukumba areas ”; 2) To find out the description of the use of school laboratories after the application of student laboratory work (AKLAM) of the Physics Education study program UIN Alauddin Makassar in the Takalar and Bulukumba areas